(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Non-steroidal anti-inflammatory drugs (NSAIDs) are a causal factor in damage to the mucous membrane of the stomach, duodenum and esophagus, triggering the development of gastroesophageal reflux disease. NSAIDs (including low-dose aspirin) are known to significantly increase the likelihood of developing peptic esophagitis, with the risk of ulceration, bleeding, or stricture formation. This article presents morphologic changes in the esophagus of white outbred rats under the drug effect of acetylsalicylic acid.